Rectus sheath haematoma: a new set of diagnostic features. Issue 926 (1st December 2002) - Maharaj, D; Ramdass, M; Teelucksingh, S; Perry, A; Naraynsingh, V
Abstract : Rectus muscle haematoma is a well documented clinical entity, but its diagnosis remains elusive. A haematoma within the rectus sheath produces a painful, tender swelling that can mimic an intraperitoneal mass with features of an acute abdomen. Two patients with rectus haematomas presenting after bouts of prolonged coughing are reported. In both cases, clinical features and ultrasound findings suggested the presence of intraperitoneal pathology. However, in both cases consistent findings in the history and examination pointed towards the diagnosis of a rectus haematoma. It is proposed that these simple clinical criteria are diagnostic of a rectus sheath haematoma, and can thereby avert an unnecessary laparotomy.